Earth-based spirituality of indigenous Filipinos: a decolonial intervention of the human-nature divide within Christian theology - Robin, Lope Balantucas; Sadje, Hadje (Postgraduate Program of State Islamic University (UIN) Salatiga Jl. Lingkar Salatiga Km. 02 Salatiga, Indonesia https://pps.uinsalatiga.ac.id/, 2025)
This paper examines the earth-based spirituality of the Igorot peoples of the Cordillera region in Northern Luzon, Philippines, as a decolonial intervention against the human–nature divide perpetuated by Western modernity and anthropocentric Christian theology. Engaging recent decolonial discussions on how coloniality shapes knowledge and representation, alongside scholarship on Cordilleran identity and contemporary indigenous religiosity, the paper addresses a persistent fragmentation between colonial genealogies, lived religion, and ethical-ecological reflection. Methodologically, the study employs a qualitative, conceptual decolonial eco-theological analysis of purposively selected secondary sources, including ethnographic and historical works on Igorot lifeworld, as well as relevant theological and decolonial literature. Through iterative close reading and thematic mapping of Igorot beliefs and practices, the analysis highlights a relational worldview in which land and the more-than-human world are understood as an interdependent sacred community. Central to this framework is the recognition of nature as inhabited by ancestral and environmental spirits (anitos), which grounds ritual reciprocity—permission-seeking, offerings, and communal rites such as the cañao—that disciplines resource use toward restraint, gratitude, and communal well-being. The paper argues that these practices constitute a decolonial moral ecology that contests colonial-capitalist logics of extraction, offering constructive implications for ecological theology, environmental ethics, and justice-oriented solidarity with Indigenous peoples.